Lower limb strength is associated with gait biomechanical abnormalities in older female fallers and non-fallers - Marques, Nise Ribeiro [UNESP]; Hallal, Camilla Zamfolini [UNESP]; Crozara, Luciano Fernandes [UNESP]; Morcelli, Mary Hellen [UNESP]; Karuka, Aline Harumi [UNESP]; Navega, Marcelo Tavella [UNESP]; Gonçalves, Mauro [UNESP] (SAGE Publications, 2013)
BACKGROUND: Age-related loss in lower limb strength is related with impaired mobility. However, the association between decreased lower limb strength and gait biomechanical abnormalities is unclear. %In line with this, With respect to these statements, our study aimed to compare the maximum isokinetic voluntary strength (MIVS) of hip, knee and ankle of older women with and without history of falls. Also, we correlate the strength of each group with gait biomechanics. METHODS: The MIVS were assessed during concentric/concentric movements performed for hip, knee and ankle joints. Gait biomechanics (kinematic and electromyography) were assessed during 1-minute recorded during the volunteers walking on the treadmill at self-selected speed. Electromyographic signal was analyzed by the linear envelop after heel strike and before toe-off. The kinematic data were analyzed using the variables: step time, length and step width and ankle angle at heel strike, and hip angle at toe-off. RESULTS: In faller group, we found that a decreased hip abduction and adduction MIVS is associated with a higher tibialis anterior activation at initial stance (p =0.04 and r =-0.53 and p=0.04 and r=-0.52). CONCLUSION: Therefore, an impaired strength of hip could causes compensation in ankle stabilizer muscles activation at initial stance in older female fallers. © 2013 - IOS Press and the authors. All rights reserved.
Keywords: Aging; EMG; fall risk; kinematic; torque; walking; abduction; adduction; aged; aging; ankle; biomechanics; clinical assessment; electromyography; female; gait; gait disorder; hip; human; kinematics; knee; parameters; strength; treadmill; walking speed